Comparison of adaptations to the engulfment model for the simulation of precipitation in confined impinging jet mixers. (10th August 2020) - Rehage, Hendrik; Scherer, Stefan; Kind, Matthias
Highlights: Three different E-model adaptations for CIJM precipitation simulation compared. Models use different initialization, coupling terms and mixing zones. Separate model initialization leads to unphysical model behavior. Empirical models perform best in predicting experimental data. Abstract: Micro mixing models are a key element for precipitation process simulation, as mixing can strongly influence the particle size distribution of the precipitate. Several adaptations to the asymmetrical engulfment model with different mixing zones and equation sets were developed to also enable the modelling of symmetrical mixers. We compare these models by analyzing the mixing mechanism, process flow sheet simulation and barium sulfate precipitation experiments. Our findings reveal different temporal evolutions of the mixing zone for the models without separate initialization. Abandoning separate initialization by integration of the initialization term into the model equations results in unphysical mechanism assumptions. By contrast, simulations using the model with the physically correct separate initialization do not predict the experimental results well. Consequently, the models without separate initialization are still the better choice for modelling fast precipitation in the setup chosen. Their empirical base should, however, be clearly indicated in future works.